New SMS classification of cochleovestibular malformation and its impact on decision-making. Issue 5 (8th May 2019) - Grover, M; Sharma, S; Preetam, C; Gupta, G; Samdani, S; Agarwal, S; Singh, S N; Sharma, M P
Abstract: Objective: To propose a new classification of inner-ear anomalies that is more clinically oriented and surgically relevant: the SMS (Sawai Man Singh) classification of cochleovestibular malformations. Methods: A retrospective multicentric study was conducted of 436 cochlear implantations carried out in 3 Indian tertiary care institutes. Patients with anomalous anatomy were included and classified, as per the new SMS classification, into cochleovestibular malformation types I, II, III and IV, based on cochlear morphology, modiolus and lamina cribrosa. Results: There were 19, 23, 8 and 4 patients with cochleovestibular malformation types I, II, III and IV, respectively. Two-year post-operative Meaningful Auditory Integration Scale scores were statistically analysed. Conclusion: This new classification for inner-ear anomalies is a simpler, more practical, outcome-oriented classification that can be used to better plan the surgery. These merits make it a more uniform classification for recording results.